Characteristics of teach-back as practiced in a university health center, and its association with patient understanding, self-efficacy, and satisfaction. Issue 11 (November 2021) - Miller, Ann Neville; Zraick, Richard; Atmakuri, Shreya; Luceno, Lisvet; Navas, Vanessa; Schmidt-Owens, Mary; Deichen, Michael; Ayers, Teresa; Thrash, Kimberley
Highlights: Recommended teach-back characteristics of plain language, non-shaming language, and avoiding yes/no questions were regularly employed by providers. Contrary to recommendations of literature, providers rarely placed the onus for understanding on themselves. Contrary to recommendations of literature, providers almost never "closed the loop" by asking patients to repeat back information until they got it correct, although patients sometimes initiated repeating back themselves after receiving clarification. Use of teach-back was associated with higher patient self-efficacy Fidelity to teach-back best practice was associated with better patient understanding of the reason for the treatment plan. Abstract: Objectives: The purpose of this research was to investigate the extent to which recommended characteristics of teach-back were employed by providers in a university Student Health Services department, and to evaluate its association with patient understanding, self-efficacy, and satisfaction. Method: The study employed a causal comparative design. Audio recordings of 87 primary care interviews were transcribed and coded for presence and characteristics of teach-back. Patients and providers filled out post-encounter questionnaires. Results: When teach-back was used, most recommended characteristics of teach-back were regularly employed. However, providers rarely placed the onus for understanding on themselves, and almost never "closed the loop" by asking patients to repeat back information until they got it correct. Teach-back was associated with higher patient self-efficacy, and high fidelity of implementation with better patient understanding of the reason for the treatment plan. Conclusions: Findings add to existing evidence regarding effectiveness of teach-back. Additional benefits may be realized when implementation is true to recommended characteristics. More research is needed into the necessity of closing the loop and placing onus on the provider. Practice implications: Given that neither patients nor providers accurately gauged the level of patient understanding in the medical encounter, teach-back may offer a simple, quick means of reinforcing provider health information and raising patient self-efficacy.